CONTINUITY IN THE PROCESS OF FORMING THE CONCEPT OF PHYSICAL QUANTITIES IN INSTITUTIONS OF PRESCHOOL AND SECONDARY EDUCATION - Колесникова, Оксана (SWorldJournal, 2020)
The implementation of the principle of continuity is considered in the work during the formation of the concept of physical quantities. The principle of continuity is considered in the work during the formation of the concept of physical quantities. Stage